Disposal Site Selection Using TOPSIS in Wonogiri District Central Java - Djunaidi, Much.; Angga, Angga; Setiawan, Eko (Universitas Muhammadiyah Surakarta, 2018)
Currently, waste is an important issue faced by almost all countries, including Indonesia, as it can have social and environmental impacts. Waste management needs coordination between local governments and waste-generating communities. The government must provide means of final waste disposal site. At present, Wonogiri District has five disposal sites located in 5 different sub-districts of Pracimantoro, Baturetno, Ngadirojo, Slogohimo and Purwantoro. Determination of alternative final disposal site in Wonogiri District is needed for more effective and optimum waste handling. Using Technique of Order Preference method by Similiary to Ideal Solution (TOPSIS), it is proposed in this article that the Baturetno site is the best alternative for final disposal site compared to the other four sites. This article also proposes a scheme for the further processing of waste into methane gas that can be utilized by the community.